Monsoon- and ENSO-driven surface-water pCO2 variation in the tropical West Pacific since the Last Glacial Maximum. (1st August 2022) - Xiong, Zhifang; Li, Tiegang; Hönisch, Bärbel; Algeo, Thomas J.; Bradtmiller, Louisa; Cane, Mark; Laj, Carlo; Wang, Fujun; Lu, Zhengyao; Qin, Bingbin; Chang, Fengming; Gong, Xun
Abstract: The East Asian monsoon (EAM) and El Niño-Southern Oscillation (ENSO) are large-scale oceanic-atmospheric fluctuations that dominate climate variability in the tropical Pacific Ocean. Although the effects of EAM and ENSO on physical and biological processes are increasingly understood, little is known about their influence on seawater carbonate chemistry in the tropical Pacific, especially in the geological past. Here, we present reconstructed variations in surface-water p CO2 ( p CO2(sw) ) and their deviation from atmospheric p CO2 (Δ p CO2(sw-atm) ) in the western Philippine Sea (WPS) since 27 ka. Our record displays covariation between Δ p CO2(sw-atm) and the intensity of the East Asian summer monsoon (EASM) since the Last Glacial Maximum (LGM), suggesting that EASM-driven upwelling controls long-term changes in surface-water carbonate chemistry and air-sea CO2 fluxes. Rapid changes in Δ p CO2(sw-atm) were linked to the ENSO-like state and, to a lesser extent, the East Asian winter monsoon (EAWM) during the Last Deglaciation, with low values corresponding to La Niña-like phases and strong EAWM during Heinrich Event 1, the Allerød and the Younger Dryas, and high values corresponding to El Niño-like phases and weak EAWM during the Bølling and Pre-Boreal. This interpretation is supported by the relationship of EAM and ENSO to modern surface-water carbonate chemistry in the WPS. Our new record, combined with previously published data, suggests that the tropical Pacific played a minimal role in sequestering CO2(atm) during the LGM. Tropical Pacific surface waters overall became a pronounced CO2 source to the atmosphere during the Last Deglaciation, possibly making a substantial contribution to the deglacial p CO2(atm) rise. We infer that this flux was mainly due to ENSO-related patterns of vertical stratification or lateral advection, perhaps in addition to equatorial upwelling of southern-sourced waters already enriched in dissolved inorganic carbon. Our findings indicate that tropical conditions (i.e., EAM and ENSO-like state) played a crucial role in glacial-interglacial p CO2(atm) changes, suggesting that this is an important area for future research into the causes of glacial p CO2(atm) cycles. Highlights: EASM controlled long-term trend of air-sea CO2 exchange in the WPS since the LGM. ENSO and EAWM caused rapid deglacial change in air-sea CO2 fluxes in the WPS. Tropical Pacific played a minimal role in atmospheric p CO2 drawdown during the LGM. Tropical Pacific contributed overall to deglacial atmospheric p CO2 rise. ENSO & equat. upwelling of southern-sourced waters led to deglacial CO2 outgassing.